Improvement of ability of class VB students SDN Indrasari 2 Martapura to solve multiplying and dividing fraction use tiered drilling - Halawati Halawati; Mayang Gadih Ranti (Math Didactic: Jurnal Pendidikan Matematika, 2020)
Multiplying and dividing fractions often become a complicated problem for elementary school students. Students have difficulty doing fraction computation on, especially on dividing fractions. The same thing happens to students of class VB SDN Indrasari 2 Martapura, who has a problem solving multiplying and dividing fractions. The effort used to solve the problem is by using a tiered drilling method. It was done because the characteristic of students who needs a structured drill which started from a simple to a complex problem. The research aims to know the improvement of activity and ability to multiplying and dividing fraction of students’ class VB SDN Indrasari 2 Martapura by learning using tiered drilling. The research method was action research. The research subjects were 21 students of class VB SDN Indrasari 2 Martapura Data was collected by Observation and test and analyzed using averages and percentages. The research subjects were student’s activity and ability to solve multiplying and dividing fractions. The results show that there is an improvement of student’s activity from the middle to very active and student’s ability to solve multiplying and dividing fraction from high to very high.